Kinerja Guru pada Sekolah Menengah Atas : Keterkaitan Budaya Organisasi dan Kompetensi - Puspitasari, Memi; Nabila, Hasna Siti (CV. Ulil Albab Corp, 2025)
This is a study that uses three variables: Organizational Culture and Competence as independent variables, and Teacher Performance as a dependent variable. The purpose of this study is to evaluate the influence of both culture and competence on teacher performance at SMAN 1 Dayeuhkolot simultaneously and gradually. This is a quantitative study using descriptive and verification analysis. In this study, the population was 60 teachers at SMAN 1 Dayeuhkolot. The technique was saturated or census sampling; questionnaires were used to collect data, and path analysis was used to analyze them. The results show that organizational culture is good, competency is good, and teacher performance at SMAN 1 Dayeuhkolot is currently relatively high. Based on the statistical test results, it can be concluded that both organizational culture and competency influence teacher performance at SMAN 1 Dayeuhkolot both simultaneously and partially. However, organizational culture has a more dominant influence on teacher performance than competency.